PjBL IMPLMENTASI MODEL PEMBELAJARAN PJBL BERBANTUAN MEDIA WORD WALL PADA MATERI NORMA DAN ATURAN KELAS V SD PANCASILA - dina muliani; Yasinta Amalia Putri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This research aims to determine the form of implementation of project-based learning with the help of word wall media on the learning outcomes of class V students at SD Pancasila regarding norms and rules. This research uses a qualitative approach with an experimental type. The method used in this research design is a descriptive qualitative method. Descriptive qualitative method is a research method that aims to describe or describe a phenomenon or situation systematically, factually and accurately. The sample used in this research involved 10 class V students at SD Pancasila. Data collection techniques in this research used observation, interview and documentation techniques. Based on the results of the research conducted, it was found that the implementation of the PjBL learning model assisted by word wall media in the material on norms and rules for class V elementary school could improve student learning outcomes. From these results it can be concluded that the word wall media used in this research can help students to remember and understand the material being studied. The word wall media contains various important terms and concepts related to norms and rules.